Effect of hydrotropes on the micellization behavior of sodium dodecyl sulfate/sodium dodecyl benzene sulfonate at various temperatures. Issue 11 (2nd November 2017) - Sheikh, Mohmad Shafi; Khanam, Ahmad Jahan; Shafi, Nusrat; Amin, Adil; Rub, Malik Abdul
ABSTRACT: With the aim of studying the effect of anionic hydrotrope sodium salicylate and nonionic hydrotrope resorcinol on the micellization behaviors of sodium dodecylsulfate (SDS) as well as sodium dodecylbenzenesulfonate (SDBS), experiments were carried out in aqueous medium at different temperatures using conductivity measurements. Hydrotrope addition leads to decrease in values of critical micelle concentration ( cmc ). The values of cmc of mixtures were obtained to be lower than the cmc value of ideal and pure component cmc values, which indicate negative deviation with synergistic interaction as confirmed by the negative interaction parameters ( β m ) values in mixed systems. In addition, the evaluated values of excess free energy of mixing ( ) as well as free energy of micellization (Δmic G ○ ) are achieved to be negative showing stability of mixed systems. GRAPHICAL ABSTRACT: